Impact of allergy and atopy on the risk of pseudophakic cystoid macular edema - Schaub, Friederike; Adler, Werner; Koenig, Meike C.; Enders, Philip; Grajewski, Rafael S.; Cursiefen, Claus; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
To assess the risk of pseudophakic cystoid macular edema (PCME) following cataract surgery in patients with allergies and/or atopic disorders.Medical records of 3,850 consecutive eyes that underwent cataract surgery were retrospectively reviewed for prevalence of allergies and atopic status and development of PCME. Patients with any known risk factors for PCME were excluded. Macular examination was performed using spectral-domain optical coherence tomography (SD-OCT) before and at 4, 8, 12, 16, 24, and 36 weeks after surgery. If both eyes in one patient underwent cataract surgery, one eye was randomly selected. Odds ratios and confidence intervals were estimated.Out of 240 patients enrolled in this series, 65 patients (27.1 %) showed positive allergic status, 19 patients (7.9 %) suffered from atopic syndromes, and 11 (4.6 %) showed both (allergies and atopic diseases). PCME occurred in eight patients (12.3 %) of the allergy cohort, whereas no patient (0 %) of the atopy cohort developed PCME. The risk of PCME was comparable in patients with allergies or atopic diseases to patients without allergies or atopy (allergy: p = 0.635; odds ratio (OR) 1.303, 95 % confidence interval (CI) 0.461-3.398; atopy: p = 0.234; OR 0.000, 95 % CI 0-1.815).Positive status of allergy or atopy does not seem to increase the risk of PCME. Therefore, postoperative treatment after cataract surgery does not have to be modified in allergic or atopic patients.
EVALuna2:5574